2 Answers | Add Yours
We'll have to use the following identity to compute tan(x - `pi` ).
`tan (a - b)` = `(tan a - tan b)/(1 + tan a*tan b)`
We'll replace a and b by x and `pi`, such as:
`tan (x - pi )` = `(tan x - tan pi)/(1 + tan x*tan pi)`
But `tan pi = sin pi/cos pi = 0/-1 = 0`
`tan (x - pi) = (tan x - 0)/(1 + tan x*0)`
`tan(x - pi) = tan x`
Therefore, the value of tangent of the difference `x - pi` remains the same as the value of the tangent of the angle x.
tan(x-pi) = (tanx - tan pi)/(1-tanx.tan pi)
we know that tan pi = 0
= (tanx - 0)/(1- tanx*0)
= tan x
We’ve answered 319,199 questions. We can answer yours, too.Ask a question